2006
DOI: 10.1038/nchembio801
|View full text |Cite
|
Sign up to set email alerts
|

Coupling ligand structure to specific conformational switches in the β2-adrenoceptor

Abstract: G protein-coupled receptors (GPCRs) regulate a wide variety of physiological functions in response to structurally diverse ligands ranging from cations and small organic molecules to peptides and glycoproteins. For many GPCRs, structurally related ligands can have diverse efficacy profiles. To investigate the process of ligand binding and activation, we used fluorescence spectroscopy to study the ability of ligands having different efficacies to induce a specific conformational change in the human beta2-adreno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
278
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(309 citation statements)
references
References 22 publications
28
278
0
1
Order By: Relevance
“…In simulations of several constitutively active mutants and of the ␤ 2 AR-T4L fusion construct, the equilibrium shifted toward conformations with the ionic lock broken and helices 3 and 6 farther apart. Our results thus suggest that an intact ionic lock is not a requirement for an inactive state of ␤ 2 AR, but rather that the wild-type receptor in the inactive state frequently adopts conformations with the ionic lock formed, in accord with biochemical observations indicating that the ionic lock stabilizes the inactive state (13,21).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…In simulations of several constitutively active mutants and of the ␤ 2 AR-T4L fusion construct, the equilibrium shifted toward conformations with the ionic lock broken and helices 3 and 6 farther apart. Our results thus suggest that an intact ionic lock is not a requirement for an inactive state of ␤ 2 AR, but rather that the wild-type receptor in the inactive state frequently adopts conformations with the ionic lock formed, in accord with biochemical observations indicating that the ionic lock stabilizes the inactive state (13,21).…”
supporting
confidence: 80%
“…Upon activation of rhodopsin, the intracellular ends of helices 3 and 6 move apart, breaking the Arg 3.50 /Glu 6.30 contact (14)(15)(16)(17). A variety of biochemical evidence has suggested that the homologous residues in many other GPCRs, including the ␤-adrenergic receptors, also form an ionic lock in the inactive state (13,(18)(19)(20)(21). Indeed, the term ''ionic lock'' was originally coined in a study of ␤ 2 AR to describe the interaction of Arg-131 3.50 with Glu-268 6.30 and Asp-130 3.49 (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of bimane quenching is dependent upon proximity to Trp as well as other factors, such as stereochemistry and local environment. The magnitude of bimane quenching by Trp in membrane proteins is typically a 10-50% change in the emission spectra, as reported with visual rhodopsin (23,24), the cyclic nucleotide-gated ion channel (25), or the β-adrenoreceptor (26).…”
mentioning
confidence: 78%
“…These studies showed that some key residues (e.g. Glu Previous mutagenesis, fluorescence and EPR studies [71,72,73,86,135,144] suggested that the disruption of the "ionic lock" as observed in the opsin* structure is induced by a rotational and translational movement of TM6. The opsin* crystal structure revealed that due to TM6…”
Section: ) Changes In Microdomains Containing the E(d)ry And Npxxy(xmentioning
confidence: 99%